Clinical and pathological features of adrenal myelolipoma and myelolipomatous metaplasia cases in our hospital over 13 years - Şensu, Sibel; Ege Gül, Aylin; Hallaç Keser, Sevinç; Gürbüz, Yeşim Saliha; Altıntaş, Mehmet; Barışık, Cem Cahit; Özdemir Barışık, Nagehan; Erdoğan, Nusret (Galenos Publishing House, 2023)
BACKGROUND/AIMS: The development and widespread use of abdominal imaging techniques has increased the incidence of unexpected adrenal tumors called adrenal incidentaloma. Adrenal myelolipomas are the second most common incidentalomas. Similar myelolipomatous morphology appears as a secondary degenerative change in other adrenal lesions and is called myelolipomatous metaplasia. This study investigated the adrenal entities of the last 13 years which had myelolipomatous components.MATERIALS AND METHODS: In this retrospective observational study, cases diagnosed as adrenal myelolipoma or myelolipomatous metaplasia between January, 2009 and January, 2022 were re-examined regarding their age, gender, localization, lesion size, and secondary histopathological changes, accompanying pathological diagnoses as well as clinical and radiological data.RESULTS: Eleven adrenal myelolipoma cases and 6 myelolipomatous metaplasia cases were detected. In myelolipomas, the mean age was 55.45 years, 73% were female and 82% were located on the right side. The lesions were encapsulated and their mean size was 7 cm. One case had a diagnosis of subclinical Cushing's syndrome and the others were hormonally inactive. Some cases were accompanied with hypertension (27%), type 2 diabetes (18%), and asthma (18%). All myelolipomatous metaplasias, which are non-encapsulated, were detected in adrenocortical adenomas. The mean age was 58 years; nonencapsulated and 67% were located on the right side with no gender predilection. Concomitant hypertension (50%), diabetes /33%, and asthma (33%) were frequent.CONCLUSION: Adrenal myelolipoma and myelolipomatous metaplasia both contain adipose and myeloid components. Myelolipoma is a benign and encapsulated neoplasia which is usually detected incidentally. They frequently coexist with chronic diseases such as hypertension, diabetes and asthma.
Keywords: Adrenal; Myelolipoma; Myelolipomatous Metaplasia